2004
DOI: 10.1088/0022-3727/37/16/016
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of travelling wave induced electrothermal fluid flow

Abstract: Many microdevices for manipulating particles and cells use electric fields to produce a motive force on the particles. The movement of particles in non-uniform electric fields is called dielectrophoresis, and the usual method of applying this effect is to pass the particle suspension over a microelectrode structure. If the suspension has a noticeable conductivity, one important side effect is that the electric field drives a substantial conduction current through the fluid, causing localized Joule-heating. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 13 publications
2
49
0
Order By: Relevance
“…Similar to those previously studied in eDEP [34][35][36][37][38][39][40][41][42][43][44][45][46][47], electrothermal flows in iDEP devices also arise from the action of the electric field (both DC and AC) on fluid inhomogeneities (predominantly electrical properties including conductivity and permittivity) formed in the constriction region due to Joule heating-induced temperature gradients. Figure 4 shows the numerically predicted temperature and electric field contours in the constriction region at 100 V DC/500 V AC.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Similar to those previously studied in eDEP [34][35][36][37][38][39][40][41][42][43][44][45][46][47], electrothermal flows in iDEP devices also arise from the action of the electric field (both DC and AC) on fluid inhomogeneities (predominantly electrical properties including conductivity and permittivity) formed in the constriction region due to Joule heating-induced temperature gradients. Figure 4 shows the numerically predicted temperature and electric field contours in the constriction region at 100 V DC/500 V AC.…”
Section: Resultssupporting
confidence: 63%
“…It has been long known in capillary electrophoresis that Joule heating can elevate the buffer temperature and disturb the electroosmotic flow causing significant sample dispersion [30][31][32][33]. The effects of Joule heating on fluid temperature and motion in eDEP have been investigated previously [34][35][36][37][38]. It was reported that a pair of counter-rotating fluid circulations could form near the microelectrodes [39].…”
Section: Introductionmentioning
confidence: 99%
“…In stark contrast, merely one dominating horizontal TWET whirlpool in the direction of signal-phase propagation is captured on the glass base at frequencies on the order of the inverse charge relaxation time of bulk fluid ( Fig.2(e)), and the rotating flow profile becomes more circular and less helically cascading with further increase in field frequency ( Fig.2(f)). Unexpectedly, however, the co-field induction vortex in current microfluidic device is opposite to the anti-field streaming of induction micropump using glass substrate from previous researchers [42]. According to preliminary mathematical analysis, this peculiar flow reversal phenomenon is originated by external natural convection on millimeter-scale highly-conductive electrode pads that substantially gives rise to an electrode cooling effect, which simultaneously makes the rotating flow velocity measured by experiments much closer to theoretical prediction compared to the traditional non-3 of 17 cooling models.…”
Section: Introductionmentioning
confidence: 54%
“…Perch-Nielsen et al have predicted that flow direction of induction pump using a glass substrate is against the signal-phase propagation [42]. The low thermal conductivity of glass material cannot effectively remove the internal electric heat generation to the ambient environment, so that the hot spots of the whole microfluidic system are positioned within the interelectrode gaps right on the channel bottom surface.…”
Section: Computational Modelmentioning
confidence: 99%
See 1 more Smart Citation